Cancer Clinical Trials—Do We Need a New Algorithm in the Age of Stratified Medicine?. (22nd May 2013) - Doroshow, James H.; Sleijfer, Stefan; Stupp, Roger; Anderson, Kenneth
Abstract : The explosion in genomic discovery science and its application in oncology in recent years is underpinning an unprecedented increase in our understanding of mechanisms underlying malignant processes. An increased understanding creates challenges pertinent to the area of cancer clinical trial development and application. Although the existing cancer clinical trial algorithm has served us well in the past, is it still fit for purpose in the 21st century?